Integrated Marketing Communication Strategy of LAZISNU in Building the ‘NU Preneur’ Brand Equity and Mobilizing Zakat Funds - Silachi Agusta Adi Putra (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2024)
This study analyzes the role of productive zakat in strengthening human and social capital among beneficiary families of the NU Preneur program managed by LAZISNU. Employing a mixed-method approach that integrates qualitative interviews and quantitative measurements, the research examines improvements in skills, financial literacy, and social network development. The findings demonstrate that productive zakat directed toward entrepreneurship and capacity building significantly enhances human capital by increasing vocational competence, self-efficacy, and economic resilience among mustahik. At the same time, it reinforces social capital through the development of trust, cooperation, and mutual support within community-based microenterprise networks. The NU Preneur program encourages beneficiaries to move beyond dependency and gradually become active contributors to their local economies. Furthermore, the integration of religious motivation and social engagement strengthens the sustainability of empowerment outcomes. By embedding Islamic ethical values such as amanah and ukhuwah, productive zakat functions not merely as financial assistance but as a catalyst for collective welfare and inclusive development. This study enriches the discourse on Islamic economic sociology and poverty alleviation by presenting zakat as a multidimensional tool for sustainable community empowerment.